Predicting response to iron supplementation in patients with active inflammatory bowel disease (PRIme): a randomised trial protocol - Andrea E van der Meulen-de Jong; Gerard Dijkstra; Zlatan Mujagic; Marjolijn Duijvestein; Rogier L Goetgebuer; Roberta Loveikyte (BMJ Open)
Introduction Iron deficiency anaemia (IDA) is the most common systemic manifestation of inflammatory bowel disease (IBD) that has detrimental effects on quality of life (QoL) and disease outcomes. Iron deficiency (ID), with or without anaemia, poses a diagnostic and therapeutic challenge in patients with IBD due to the multifactorial nature of ID(A) and its frequent recurrence. Elevated hepcidin—a systemic iron regulator that modulates systemic iron availability and intestinal iron absorption—has been associated with oral iron malabsorption in IBD. Therefore, hepcidin could assist in therapeutic decision-making. In this study, we investigate whether hepcidin can predict response to oral and intravenous iron supplementation in patients with active IBD undergoing anti-inflammatory treatment.Methods and analysis PRIme is an exploratory, multicentre, open-label and randomised trial. All adult patients with active IBD and ID(A) will be assessed for eligibility. The participants (n=90) will be recruited at five academic hospitals within the Netherlands and randomised into three groups (1:1:1): oral ferrous fumarate, oral ferric maltol or intravenous iron. Clinical and biochemical data will be collected at the baseline and after 6, 14 and 24 weeks. Blood samples will be collected to measure hepcidin and other biomarkers related to iron status. In addition, patient-reported outcomes regarding QoL and disease burden will be evaluated. The primary outcome is the utility of hepcidin as a predictive biomarker for response to iron therapy, which will be assessed using receiver operating curve analysis.Ethics and dissemination The study has been approved by the Institutional Review Board at the Leiden University Medical Center (IRB No. P21.109) and other study sites. All participants will provide written informed consent to enrol in the study. The findings will be published in a peer-reviewed journal and disseminated at scientific conferences; the dataset will be available on reasonable request.Trial registration Prospectively registered in the https://clinicaltrials.gov/ and the Eudra registries. First submitted on 10 May 2022 to the ClinicalTrials.gov (ID: NCT05456932) and on 3 March 2022 to the European Union Drug Regulating Authorities Clinical Trials Database (ID: 2022-000894-16).